"Det er veldig forskjellig fra hjemlandet mitt" - Kathrine Rønning Tvinnereim; Gunnhild Bergset (Nordic Journal of Comparative and International Education, 2023)
This article presents an interview study with seven parents with migration backgrounds who have children in Early Childhood Education and Care institutions (ECEC). It highlights the parents’ experiences related to their interaction with ECECs during their first year as ECEC parents. The aim of the study is to explore how parents with migration backgrounds experience communication and interaction with ECEC staff.